Comparative Effect of Different Mulches on Structural and Hydraulic Properties of Soil under Nectarine - Kumar, Amit; Verma, Sudhir (International Journal of Economic Plants, 2021)
A field study was conducted at the research farm of the Department of Soil Science and Water Management, Nauni, Solan to study the effect of different mulches on structural and hydraulic properties of soil under Nectarine cv. Silver King”. Application of different mulch treatments viz. No Mulch (UM), Grass Mulch (GM), Black polythene Mulch (BP), Pine Needle Mulch (PM), Transparent polythene Mulch (TM), Silver polythene Mulch (SM) and Mulch Mat (MM) resulted in significant changes in soil properties at 0-7.5 and 7.5- 15 cm depths. The bulk density (ρb) was lowest (1.27 and 1.29 Mg m-3) and total porosity (f) was highest (51.96 and 50.57 %) under GM at 0-7.5 and 7.5-15 cm soil depth, respectively. The highest proportion of WSA >0.25 mm (67.20 and 63.90 %) was recorded under T2 -GM and the lowest (60.77 and 58.83%) was observed under T3 –BP, in 0-7.5 and 7.5-15.0 cm soil depth, respectively. The highest mean weight diameter (MWD) of soil aggregates (2.25 mm and 2.23 mm) was found in T3 (BP) at both 0-7.5 cm and 7.5-15 cm soil depth, respectively. Highest saturated hydraulic conductivity (Ks) was recorded under T2 -GM (4.45 cm hr-1), and lowest Ks was observed under T3 -BP (3.50 cm hr-1). Among all the different mulch treatments, black polythene mulch (BP) mulch was found superior in conserving soil moisture as compared to all other treatments at both the soil depths. The highest soil moisture content, w during the cropping season under treatment T3 (BP) at 0-7.5 and 7.5-15 cm ranged between 16.7-19.7 and 18.0-20.8% with mean values of 18.0 and 19.1%, respectively, followed by treatment T7 (MM) with w ranging from 16.4-19.7 and 17.7-20.8% with mean values of 17.8 and 18.9%, respectively. The lowest w was recorded under the T1 (UM), which ranged between 13.7-16.1 and 16.0-18.6% with average value of 15.4 and 17.5% at 0-7.5 and 7.5-15 cm soil depth, respectively. Highest values for maximum water holding capacity (MWHC), field capacity (FC) and permanent wilting point (PWP) were recorded under T2 (GM).